ANALYSIS OF THE APPLICATION OF ACCOUNTING STANDARDS TO SMALL AND MEDIUM ENTERPRISES OF DODOL ENTREPRENEURS IN HULU SUNGAI SELATAN DISTRICT - Syariah; Fraick Nicky Gillian Ratumbuysang, Monry; Rizky, Maulana; Hasanah, Mahmudah (Manager : Jurnal Ilmu Manajemen, 2023)
In terms of financial records, the government has established the preparation of financial reports for MSMEs, namely SAK EMKM (Standards for Financial Accounting for Micro, Small and Medium Entities). Financial reports are generated through a procedure that is commonly referred to as the accounting cycle. This study aims to describe the application of accounting standards to small and medium enterprises of dodol entrepreneurs in Hulu Sungai Selatan Regency. The research method used is descriptive analysis with a qualitative approach. The research subjects consisted of seven MSME dodol entrepreneurs in Hulu Sungai Selatan Regency. Data collection techniques using observation, interviews and documentation. Test the validity of the data in this study using triangulation. The data analysis techniques used are data reduction, data display, and verification or drawing conclusions. The results of the study show that MSME dodol entrepreneurs in Hulu Sungai Selatan Regency have not yet implemented it accounting standards as a whole up to the reporting stage accountability in a period, business actors only do Keeping proof of transactions and recording ordinary journals. This is due to by several obstacles, including the lack of knowledge of business actors regarding accounting records, the assumption that between owners and employees are close relatives, and because the educational background of dodol business actors related to accounting is very low.